ANALISIS RESIKO KESELAMATAN DAN KESEHATAN KERJA PADA PT RHODA BAKTI JAYA MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY (HAZOPS) - Bayu Eko Prastyo; Andung Jati Nugroho (CV. ALIM'SPUBLISHING, 2025)
PT Rhoda Bakti Jaya is a company located on Jl. Pegangsaan Dua, Blok A1 Km 1.6, Kelapa Gading, Rt 05 / Rw 02 Kec. Kelapa Gading, North Jakarta .PT Rhoda Bakti Jaya is a company engaged in manufacturing PT. Rhoda Bakti Jaya is a company operating in the industrial sector which is located at JL. Pegangsaan Dua, Blok A1 Km 1.6, Kelapa Gading, Rt 05/ Rw 02 Kec. Kelapa Gading, North Jakarta. This company produces various types of components for trucks, namely truck frame or chassis components, brake components and pistons and brake cylinders. This job has a high risk of accidents so that it causes many accidents to workers. Therefore, in this research, using the HAZOP method, we can analyze the level of risk using likelihood, consequences and put it into the risx matrix scale.